Too Masculine for Words. Masculinity and Leadership in Post-apartheid South Africa - Claudia Ortu (Medea, 2020)
The article looks at the relationship between masculinities and power in post-apartheid South Africa through the lenses of social semiotics. The way in which former President of the Republic of South Africa Jacob Zuma construed and performed his own masculinity throughout his period in office will be contrasted with the criticism of his behaviour in editorial cartoons and paintings.